\(\lambda(\mu\vec{v}) = (\lambda\mu)\vec{v}\)

$$\begin{align}
\lambda(\mu\vec{v})
&= \lambda\left(\mu\begin{bmatrix}v_1 \\ \vdots \\ v_n\end{bmatrix}\right) \\[1em]
&= \lambda\begin{bmatrix}\mu v_1 \\ \vdots \\ \mu v_n\end{bmatrix} \\[1em]
&= \begin{bmatrix}\lambda(\mu v_1) \\ \vdots \\ \lambda(\mu v_n)\end{bmatrix} \\[1em]
&= \begin{bmatrix}\lambda\mu v_1 \\ \vdots \\ \lambda\mu v_n\end{bmatrix} \\[1em]
&= (\lambda\mu)\begin{bmatrix}v_1 \\ \vdots \\ v_n\end{bmatrix} \\[1em]
&= (\lambda\mu)\vec{v} &\blacksquare
\end{align}$$